Relatório de Estágio Profissional: "O início de um sonho começa pela primeira caminhada - os primeiros passos" - André Daniel Magalhães Gonçalves (2019)
The School Placement was drafted within the scope of the Professional Internship Curricular Unit. It´s mandatory to obtain the Master degree in Physical Education in Basic and Secondary Education at the Faculty of Sport, University of Porto. Throughout the document the experiences during the internship year and the tasks developed by the EE, in the internship context, are portrayed. The Professional Internship took place under the guidance of the Cooperating Teacher of the Faculty of Sport, University of Porto, in a Cooperative School in Porto city center, where the Supervised Internship Practice was held. The document is divided into eight main points, which details the experiences obtained during the professional development process, based on the reflexion of the EE itself, but also on the dialogue with the Internship pairs, as well as with the others promoters of teaching of the school. During the internship, the contents learned in previous years are put into practice, in a real context and with a resident and shared class, making the whole process unique and full of meaningful learning. The report contains an Research-Action study applied in one of the classes, whose objective was to improve and increase the transmission of feedback from the EE. At the end of this report, there's room for a concluding reflexion about this very important step in the academic education, along with the prospects for the future.